The Effect of Physical Practice and Selective and Compulsive 0bservational Pattern on Inner Motivation and Cognitive Learning of Basketball Jump Shot: with regard to the basic Psychological Needs - Farzad Maleki; Mahmood Sheikh; Fazlallah Bagherzadeh; Rasoul Hemayattalab (University of Tehran, 2022)
Introduction: This research aimed to investigate the effect of physical training and selective and compulsory observational pattern on the intrinsic motivation and cognitive learning of basketball jump shot skill with the approach of basic psychological demands.Methods: Eighty male students (18-22 years old) were selected voluntarily and based on their pre-test scores, were randomly divided into four Self-Control, Paired, Experimenter-Control, and Control groups (20 people in each group). To examine the motivation level, the Intrinsic Motivation Inventory (IMI), and to examine the cognitive learning level, Recall Questionnaire (adapted from Knudson, 1993) was used. An educational video of the expert model that showed the movement components was presented to the participants. A retention test was conducted 24 hours later. One-way analysis of variance (ANOVA) was used to examine the data (p≥0.05).Results: The results showed that in the acquisition phase, the level of intrinsic motivation of the participants to learn the basketball jump shot skill in the Self-Control observation condition was significantly higher than the participants in the Paired and Control conditions. Also, in the retention phase, the level of intrinsic motivation in the Self-Control observation condition was significantly higher than in other experimental conditions. In addition, in the acquisition and retention phases of cognitive learning (recall success), the participants in the Self-Control observation condition scored significantly higher than the participants in the Paired and Control conditions.Conclusion: In general, the results of this study show that motivation affects learning. Also, task demonstration as a whole-part-whole is an effective and efficient method in the cognitive phase.